2022
DOI: 10.2147/jaa.s345759
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Serum Cytokine Profile in Allergic Asthma Patients According to Disease Severity

Abstract: Purpose Allergic asthma is a heterogeneous disease with complex underlying mechanisms. Cytokines are key mediators in immune system and potential indicators of disease status. The aim of this study is to compare the difference of serum cytokine profile in allergic asthma patients with different disease severity and explore candidate biomarkers for disease monitoring and targeting therapeutic agents. Patients and Methods A total of 40 allergic asthmatics (mild, n=22; mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…studies have demonstrated the pivotal role of MCP-3 in distinguishing between infectious and non-infectious diseases. Research by Sun L’s team indicates the potential utility of serum MCP-3 levels in distinguishing between patients with mild and severe asthma ( 21 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…studies have demonstrated the pivotal role of MCP-3 in distinguishing between infectious and non-infectious diseases. Research by Sun L’s team indicates the potential utility of serum MCP-3 levels in distinguishing between patients with mild and severe asthma ( 21 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…studies have demonstrated the pivotal role of MCP-3 in distinguishing between infectious and non-infectious diseases. Research by Sun L's team indicates the potential utility of serum MCP-3 levels in distinguishing between patients with mild and severe asthma (21). Yang et al examined 48 cytokines in the peripheral blood of COVID-19 patients, identifying IP-10, MCP-3, and IL-1ra as biomarkers associated with disease severity and fatal outcomes (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En el reciente trabajo de Sun et al (2022) 15 se comparó el perfil de expresión de citoquinas séricas entre pacientes con AA de diverso grado de gravedad y se buscaron biomarcadores útiles para el seguimiento de la enfermedad y la elección de agentes terapéuticos. En este estudio se concluyó que las proteínas YKL-40, eotaxina-1 y MCP-1 podrían ser biomarcadores candidatos para reflejar la gravedad de los pacientes con AA.…”
Section: Diagnóstico Y Fenotipado Del Aagunclassified